Biallelic mutations in MOS cause female infertility characterized by human early embryonic arrest and fragmentation. Issue 12 (15th November 2021) - Zhang, Yin‐Li; Zheng, Wei; Ren, Peipei; Hu, Huiling; Tong, Xiaomei; Zhang, Shuo‐Ping; Li, Xiang; Wang, Haichao; Jiang, Jun‐Chao; Jin, Jiamin; Yang, Weijie; Cao, Lanrui; et al.
Abstract: Early embryonic arrest and fragmentation (EEAF) is a common phenomenon leading to female infertility, but the genetic determinants remain largely unknown. The Moloney sarcoma oncogene ( MOS ) encodes a serine/threonine kinase that activates the ERK signaling cascade during oocyte maturation in vertebrates. Here, we identified four rare variants of MOS in three infertile female individuals with EEAF that followed a recessive inheritance pattern. These MOS variants encoded proteins that resulted in decreased phosphorylated ERK1/2 level in cells and oocytes, and displayed attenuated rescuing effects on cortical F‐actin assembly. Using oocyte‐specific Erk1/2 knockout mice, we verified that MOS‐ERK signal pathway inactivation in oocytes caused EEAF as human. The RNA sequencing data revealed that maternal mRNA clearance was disrupted in human mature oocytes either with MOS homozygous variant or with U0126 treatment, especially genes relative to mitochondrial function. Mitochondrial dysfunction was observed in oocytes with ERK1/2 deficiency or inactivation. In conclusion, this study not only uncovers biallelic MOS variants causes EEAF but also demonstrates that MOS‐ERK signaling pathway drives human oocyte cytoplasmic maturation to prevent EEAF. SYNOPSIS: Biallelic variants in MOS gene cause recurrent early embryonic arrest and fragmentation (EEAF) and female infertility. MOS variants impair activation of MOS‐ERK signal cascade, prevent substantial maternal mRNAs decay and hamper embryonic development both in human and mice. Four rare variants in MOS gene were identified in three Chinese infertile females displaying EEAF followed recessive inheritance pattern. Mutant MOS proteins failed to activate ERK1/2 cascade, and Erk1/2 ‐deficient mice also exhibited EEAF, confirming the human diagnostic. MOS‐ERK1/2 signal cascade is required for maternal mRNA clearance during human oocyte maturation, especially of transcripts relative to mitochondrial function. Inactivation of human or mouse MOS‐ERK1/2 signal cascade caused mitochondrial dysfunction in mature oocytes. Abstract : Biallelic variants in MOS gene cause recurrent early embryonic arrest and fragmentation (EEAF) and female infertility. MOS variants impair activation of MOS‐ERK signal cascade, prevent substantial maternal mRNAs decay and hamper embryonic development both in human and mice.